2002
DOI: 10.1093/carcin/23.6.1003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of DNA repair and xenobiotic-metabolizing enzymes: role in mutagen sensitivity

Abstract: Mutagen sensitivity, measuring the extent of chromosome damage induced by an in vitro treatment of peripheral lymphocytes with bleomycin, has been associated with an increased risk of various human cancers. Sensitivity to bleomycin appears to have high heritability and is usually considered to reflect individual capacity to repair DNA lesions. Another potential contributor to variation in bleomycin sensitivity could be inherited differences in the metabolism of bleomycin. We assessed whether genetic polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
70
1
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(86 citation statements)
references
References 37 publications
11
70
1
4
Order By: Relevance
“…The mutations of XRCC1 polymorphisms may increase the risk of cancers by impairing the interaction of XRCC1 with other enzymatic proteins and consequently altering DNA repair activity (Basso et al, 2007;Tudek, 2007), and resulted in carcinogenesis development. Our study found significant an odds ratio of codon 399 Gln allele for ovarian cancer, which strongly implicates that these polymorphisms may alter the normal protein function by encoding for a twisted protein (Tuimala et al, 2002), resulting in altered affinity to its interactive proteins suggesting an association with a deficiency in DNA repair capacity. This finding indicated the XRCC1 gene variants in the impairment of DNA repair mechanism and their consequent biological effect could induce the carcinogenesis.…”
Section: Discussionsupporting
confidence: 57%
“…The mutations of XRCC1 polymorphisms may increase the risk of cancers by impairing the interaction of XRCC1 with other enzymatic proteins and consequently altering DNA repair activity (Basso et al, 2007;Tudek, 2007), and resulted in carcinogenesis development. Our study found significant an odds ratio of codon 399 Gln allele for ovarian cancer, which strongly implicates that these polymorphisms may alter the normal protein function by encoding for a twisted protein (Tuimala et al, 2002), resulting in altered affinity to its interactive proteins suggesting an association with a deficiency in DNA repair capacity. This finding indicated the XRCC1 gene variants in the impairment of DNA repair mechanism and their consequent biological effect could induce the carcinogenesis.…”
Section: Discussionsupporting
confidence: 57%
“…Even though devoid of any known enzymatic activity, XRCC1 is thought to act as a scaffold protein, play a coordinating role for consecutive stages of the BER system (Ladiges, 2006), The XRCC1 Arg399Gln polymorphism is located within the XRCC1 BRCA1 carboxyl-terminal domain (BRCT I) and is hypothesized to have functional significance because it is located within a well-conserved region and encodes a nonconservative amino acid change. However, studies examining its relation with markers of DNA damage or DNA repair function have yielded mixed results, with some studies showing a positive relation (Duell et al, 2002;Qu and Morimoto, 2005) and others observing no relation with the variants (Palli et al, 2001;Pastorelli et al, 2002;Tuimala et al, 2002;Hu et al, 2005;Leng et al, 2005;Laantri et al, 2011 ). In present study we found homozygous variants of XRCC1 Arg399Gln had observably associations with NPC risk.…”
Section: Discussionsupporting
confidence: 42%
“…These results support the notion that the aetiology of childhood ALL is more likely to depend upon interactions of many genes from different metabolic pathways, such as carcinogen metabolism and DNA repair. This is supported by a recent report indicating that mutagen sensitivity in lymphocytes of certain individuals could be associated with DNA variants in DNA repair and xenobioticmetabolizing enzymes (Tuimala et al, 2002). Other mechanisms involving MMR proteins cannot be completely ruled out, because these proteins participate in different vital cellular processes, including homologous recombination (de Wind et al, 1995), G2 checkpoint control (Hawn et al, 1995), recognition of DNA damage and/or apoptosis (Kat et al, 1993), as well as in transcription-coupled repair (Mellon et al, 1996).…”
Section: Discussionmentioning
confidence: 91%